Accelerating adoption process in the biased context: The significance of diffused information and consumer knowledge - TRAN, Thu Thanh (Edelweiss Applied Science and Technology, 2025)
This paper explores the dynamics of the personal adoption process, specifically focusing on how diffused information and consumer knowledge can accelerate the acceptance of experienced products. The study employs an experimental approach to investigate the multifaceted impacts of brand information on consumer behavior, using newly launched Japanese beef in the Vietnamese market as a case study. Through a direct survey of 480 consumers and a rigorous two-stage analysis, the study evaluates the interplay between individual knowledge and diffused information in shaping adoption behaviors. The findings indicate that enhancing brand information during the introduction phase significantly boosts consumer adoption. Moreover, the influence of information wanes over time, emphasizing the necessity for ongoing marketing efforts. These insights underscore the importance of customizing information strategies to bridge knowledge gaps and mitigate biases, ultimately facilitating the successful market entry and adoption of new products.